Targeting of CD133+ cancer stem cells by mesenchymal stem cell expressing TRAIL reveals a prospective role of apoptotic gene regulation in non-small cell lung cancer - Shaik M. Fakiruddin, Shaik Ahmad Kamal; Lim, Moon Nian; Nordin, Norshariza; Rosli, Rozita; Zakaria, Zubaidah; Abdullah, Syahrilnizam (MDPI, 2019)
Mesenchymal stem cells (MSCs) are emerging as vehicles for anti-tumor cytotherapy; however, investigation on its efficacy to target a specific cancer stem cell (CSC) population in non-small cell lung cancer (NSCLC) is lacking. Using assays to evaluate cell proliferation, apoptosis, and gene expression, we investigated the efficacy of MSCs expressing tumour necrosis factor (TNF)-related apoptosis inducing ligand (MSC-TRAIL) to target and destroy CD133+ (prominin-1 positive) NSCLC-derived CSCs. Characterization of TRAIL death receptor 5 (DR5) revealed that it was highly expressed in the CD133+ CSCs of both H460 and H2170 cell lines. The human MSC-TRAIL generated in the study maintained its multipotent characteristics, and caused significant tumor cell inhibition in NSCLC-derived CSCs in a co-culture. The MSC-TRAIL induced an increase in annexin V expression, an indicator of apoptosis in H460 and H2170 derived CD133+ CSCs. Through investigation of mitochondria membrane potential, we found that MSC-TRAIL was capable of inducing intrinsic apoptosis to the CSCs. Using pathway-specific gene expression profiling, we uncovered candidate genes such as NFKB1, BAG3, MCL1, GADD45A, and HRK in CD133+ CSCs, which, if targeted, might increase the sensitivity of NSCLC to MSC-TRAIL-mediated inhibition. As such, our findings add credibility to the utilization of MSC-TRAIL for the treatment of NSCLC through targeting of CD133+ CSCs.